2004
DOI: 10.1097/00008480-200402000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Overuse injuries in pediatric athletes

Abstract: In summary, because the number of these injuries is on the rise, it is important for the physician to be aware of the clinical manifestations of overuse injuries, to prescribe current recommended treatments, and to educate patients in proper athletic conditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 16 publications
0
31
0
2
Order By: Relevance
“…69,79 Although some authors have suggested that RTP should only be allowed after complete resolution of symptoms, 17,30,69,78,79 the proposed model clearly demonstrates why these individual components cannot be considered in isolation. 69,79 Although some authors have suggested that RTP should only be allowed after complete resolution of symptoms, 17,30,69,78,79 the proposed model clearly demonstrates why these individual components cannot be considered in isolation.…”
Section: Specific Considerations For Rtp Decision Makingmentioning
confidence: 95%
“…69,79 Although some authors have suggested that RTP should only be allowed after complete resolution of symptoms, 17,30,69,78,79 the proposed model clearly demonstrates why these individual components cannot be considered in isolation. 69,79 Although some authors have suggested that RTP should only be allowed after complete resolution of symptoms, 17,30,69,78,79 the proposed model clearly demonstrates why these individual components cannot be considered in isolation.…”
Section: Specific Considerations For Rtp Decision Makingmentioning
confidence: 95%
“…For MSK conditions caused by injury, the mantra ‘rest, ice, compression and elevation’ is often recommended, although existing evidence is equivocal 7 . Non-steroidal anti-inflammatory drugs (NSAIDs) and physical therapy also play an important role in recovery 8 . For chronic inflammatory conditions, steroids and disease-modifying antirheumatic drugs (DMARDs) have become the standard of care, but many children are left with pain despite outward evidence that inflammation has been suppressed 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The shoulder is among the most common sites of injuries in pediatric athletes (17,18). Acute injuries are usually seen in contact sports, such as football, wrestling, and hockey, whereas chronic overuse injuries are common in swimmers and baseball and tennis players (17,19). Common acute injury patterns seen in contact sports, such as midclavicular fractures, fractures of the humeral shaft, acromioclavicular separation, and glenohumeral dislocation, are similar to the same injuries seen in adults.…”
Section: Shoulder Injuriesmentioning
confidence: 99%